PERKIRAAN DAMPAK KRISIS KEUANGAN TERHADAP EKONOMI, KHUSUSNYA SEKTOR PERTANIAN DAN AGRIBISNIS DI INDONESIA - MANGARA TAMBUNAN (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2001)
Beginning from the monetary crisis of Bath-Thailand, then gradually to spread tosouth-east Asia Countries and finally has been Indonesia monetary crisis started the thirdweek in July 1997. Monetary crisis this time to indicate that Indonesia economics more andmore open and integrated with world economics. Really Indonesia to face three kind crisisi.e.: (1) Exchange rate crisis where depreciation of rupiah value toward dollars, (2) foreigndebt crisis in big quantity, which made by private and government, and (3) probably soinfected by diminishing expectation of the community toward various of economics andfinancial institutionsTo measure the impact of monetary crisis toward quantitatively economics can be notacted now yet. What that can be acted is to expect its impacts toward economics, especially toagriculture or agribusiness sectors. For need of this research-collected macroeconomics datain the last time that sources from secondary data, processed and analyzed. Because thisresearch especially to expect the impact of monetary crisis toward agriculture or agribusinesssectors, so the agriculture data collected, processed and analyzed detailer.The result of analysis to indicate that monetary crisis in Indonesia that indicated by hasbeen weak of rupiah value to dollars, has impact toward agriculture or agribusiness sectors.Yet, impact intensity depend on: (1) sources of raw material (domestic or foreign), (2)structure of output marketing for domestic or international, and (3) structure of capital, equityand firm portfolio of agribusiness mentioned. Viewed from costly structure and return, soportion of import of input and export of output in agriculture sector significantly to influencetoward performance of agriculture or agribusiness sectors.For the agriculture or agribusiness firms that using domestic raw material in theirsproduction process, monetary crisis maybe not influence so big, if mostly theirs outputexported, this crisis will positive impact. Yet, if agriculture or agribusiness firms using rawmaterial from foreign in its production process (example cotton), monetary crisis has influencetoward costs structure (increase the cost of input and output per unit) to be bigger. If theirsoutput market for domestic, so will be gloomier. In this condition, monetary crisis has negativeinfluence toward performance of agribusiness mentioned.Result of the monetary crisis, need be acted a reevaluation to measure rate of return(ROI) investment in agriculture sector. In the last time ROR in agriculture sector only range15 percent. Not impossible if this monetary crisis has made the populace agriculture is notinteresting for investor.